The structure of technical and tactical activities of water polo players in the first Yugoslav league during the game - Dopsaj, M.; Matkovic, I. (Biomechanics and Medicine in Swimming VIII, 1999)
The aim of the research was to study the structure of technical and tactical activities of water polo players in the First Yugoslav League during the game. The sample included nine top Yugoslav water polo players and the total of nine water polo games were analysed. This research covered the following variables: passing the ball, receiving the ball and shooting. The variables were observed in relation to the frequency of performing the elements, in relation to distance (short= up to 5m, middle = 5-lOm and long= over !Om), and in relation to the efficacy of performing the elements. The variables were also observed in relation to absolute values (whole game) and relative values (each quarter). A player performs the average of 38.75±14.49 passes per game (9.13, 10, 11 and 8.63 passes per quarters, respectively), 32.13±9.55 receivings (7.88, 8.63, 8.75 and 6.88 receivings per quarters, respectively) and 7.88±3.14 shoots (2.38, 2.25, 1.25 and 2 shoots per quarters, respectively). The efficacy of the elements of passing and receiving the ball is very high (88.97% and 95.48%, respectively) and it does not change per quarters (F=0.363, p=0.78; F=0.361, p=0.77, respectively). The efficacyof shooting is 54.02±18.5% and it also does not change in relation to quarters observed (F=1.27, p=0.307). However, the efficacy of shooting from middle distances changes in a statistically significant way, the least being in the first and the fourth quarters (50% and 25%, respectively), which also holds for the efficacy of shooting from long distances, the least being in the fourth quarter. During the process of training water polo teams in the Yugoslav Water Polo League, trainers should insist on increasing the efficacy of shooting from middle and long distances under the conditions of progressive fatigue.